Addiction and the law - Aoun, Elie G. (American Psychiatric Association Publishing, 2024)
"There are innumerable interface issues between those with substance use disorders SUDs and the law. Individuals with SUDs may be facing legal issues-whether through arrest, incarceration, driving-under-the-influence offenses, child custody disputes, employment issues, or court-ordered drug testing. Administrative, regulatory, and legal systems often play a critical role in how substance problems are addressed, and the result is often quite difficult, given the awkward fit between current scientific and medical views and the black-and-white provisions of often-outdated laws. Only by understanding the basics of both SUDs and governing laws can the practitioner navigate both systems in a manner that is both evidence informed and relevant to the matter at hand. This book gives an overview of the many areas in which SUDs and the law overlap. It also provides a guide to 1. the specific ways in which SUDs are treated in the U.S. legal system; 2. important SUD-related factors for judges, juries, human resources professionals, employment administrators, and others to consider; and 3, the ways in which health care providers, forensic practitioners, and legal professionals can render opinions and even advise their patients and clients, respectively. Chapters include information about legal regulation, legal structures for treatment, employment law, testing, pregnancy and children, incarceration, and other special topics. This book will appeal to all mental health clinicians, including treating clinicians and forensic psychiatrists as well as other forensic mental health professionals, legal professionals, and advocates who encounter cases in which the medical management of addictive disorders intersects with the law"-- Provided by publisher